2010
DOI: 10.1002/j.2334-5837.2010.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

1.3.1 Design principles for Ultra‐Large‐Scale (ULS) Systems

Abstract: Ultra-Large-scale Systems (ULSS) This paper recommends ten design principles and five design practices for ULS systems, drawing on known systems engineering practice and an understanding of how complexity science is applied in other domains. The paper offers practitioners a strategy and a practical approach to deal with ULS systems -or indeed any system that is larger scale and more complex than those they are accustomed to dealing with -and shows academics some possible routes to addressing the research chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…This leads to the hypothesis that if we can recognise such repeating laws and patterns, we can transfer experience, knowledge and predictions. (Sillitto, 2010) suggests that this is a very important principle in the design or management of Ultra-Large Scale Systems, and illustrates examples of complex behaviour from well-characterised fields of physics, which seem to read across into socio-technical systems. The essence of these various perspectives is summarized in two sets of statements in the following tables: one set in the style of "a system is (or does)", the other in the style of "a system may".…”
Section: Generic System Theories and Modelsmentioning
confidence: 95%
“…This leads to the hypothesis that if we can recognise such repeating laws and patterns, we can transfer experience, knowledge and predictions. (Sillitto, 2010) suggests that this is a very important principle in the design or management of Ultra-Large Scale Systems, and illustrates examples of complex behaviour from well-characterised fields of physics, which seem to read across into socio-technical systems. The essence of these various perspectives is summarized in two sets of statements in the following tables: one set in the style of "a system is (or does)", the other in the style of "a system may".…”
Section: Generic System Theories and Modelsmentioning
confidence: 95%
“…• Application of systems thinking and a systems engineering approach to design tool-chain architecture (Anon 2011) (Cloutier et al 2015) • Use of a SPIT based framework for structuring viewpoints (Jinzhi 2016) (Sillitto 2010) • A model-based approach to support tool-chain development…”
Section: A System Thinking Way To Develop Mbse Tool-chainmentioning
confidence: 99%
“…However, since the collected viewpoints are unstructured and wide in scope, it is difficult to organize and analyze them in a systematic way. Therefore as illustrated in Table 3, we make use of a slightly revised SPIT framework oriented from (Sillitto 2010) to arrange and classify these viewpoints into four views: Social, Process, Information and Technique (Jinzhi 2016). From the business case for systems engineering study (Elm & Goldenson 2012), we found that a project plan and project monitoring and control are important factors influencing project performance when the research team adapts a system engineering approach.…”
Section: Spit Frameworkmentioning
confidence: 99%
“…The idea of having to be 100% clear on the requirements for a system element before starting work on it is plainly impractical and wrong (Beasley et al, 2014). The idea of a "wicked problem" shows that very often it is only by considering a potential solution can the requirements be considered (see Sillitto , 2010, andConklin, 2005 This leads to the idea that "requirements understanding" is concurrent with "solution development". This is developed much further in the idea of the spiral development model (see Boehm et al, 2014).…”
Section: Introductionmentioning
confidence: 99%